Econometric Analysis of the Impact of Energy Subsidy Policies on Household Consumption Patterns in Indonesia - Putri, Fitri Ayu Triana (Sekolah Tinggi Agama Islam Kuningan, 2025)
This study aims to analyze the impact of energy subsidy policies on household consumption patterns in Indonesia. Energy subsidies, which are provided to ease the economic burden on households, have a significant influence on energy consumption, especially in increasing household energy use. This study employs a qualitative method, incorporating in-depth interviews, questionnaires, and observations of households that receive energy subsidies. The results show that households that receive subsidies tend to consume more energy, albeit at a more affordable cost. The untargeted distribution of subsidies results in energy waste, as some wealthy households continue to receive subsidies. Although subsidies provide social benefits, their impact on energy consumption behavior shows the need for educational programs on energy efficiency and improved subsidy distribution mechanisms. The study also found that energy subsidy policies should be balanced with more sustainable policies, such as the use of renewable energy and incentives for energy efficiency. The practical implication of this study is the importance of evaluating energy subsidy policies to be more targeted and supported by educational programs that can increase public awareness of efficient energy use.